Global trends and research mental health counseling: a bibliometrics analysis - Ifdil, Ifdil; Zola, Nilma; Pratiwi Fadli, Rima; Zatrahadi, M. Fahli (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
The topic of mental health counseling is one that is now being explored quite a bit. The significance of preserving mental health is becoming increasingly clear to people. We use network visualization and quantitative bibliometric analysis to identify research trends and focus areas. We hope that this research will serve as a guide for upcoming follow-up research by outlining trends in mental health counseling research. The Scopus database's relevant English publications were taken out. The coauthorship networks of authors, nations, and the cooccurrence networks of author keywords were constructed using VOSviewer (version 1.6.17). We analyzed 452 articles published using the term